Signal and Information Processing, Networking and Computers Proceedings of the 5th International Conference on Signal and Information Processing, Networking and Computers (ICSINC) - Sun, Songlin; Fu, Meixia; Xu, Lexi.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This proceedings book presents selected papers from the 5th Conference on Signal and Information Processing, Networking and Computers (ICSINC), held in Yuzhou, China, from November 29 to December 1, 2018. It focuses on the current research in a wide range of areas in the fields of information theory, communication systems, computer science, signal processing, aerospace technologies, and other related technologies. With contributions from experts from both academia and industry, it is a valuable resource for anyone who is interested in this field.
Big Data Analytics -- Compressed Sensing -- Information Theory & Statistics -- Quantum Information & Coding Theory -- Spectrum Estimation & Modeling -- Spectrum Shaping & Filters -- Signal Detection and Synchronization -- Signal Processing in Networked Systems -- Pattern Recognition & Learning -- AI & Neural Networks -- Machine Learning.
Keywords: Signal processing; Big data; Telecommunication; Aerospace engineering; Astronautics; Signal, Speech and Image Processing; Big Data; Communications Engineering, Networks; Aerospace Technology and Astronautics